Analysis of Portuguese Architectural Heritage Techniques and Protection in Maputo, Mozambique - Junxin Song (PT FORMOSA CENDEKIA GLOBAL, 2022)
This article mainly analyzes the architectural heritage of Maputo, Mozambique. These include a large number of Portuguese-style buildings with period skills. Finally, the reference suggestions for protection measures are put forward.